2017
DOI: 10.1016/j.tox.2016.05.022
|View full text |Cite
|
Sign up to set email alerts
|

An autophagic process is activated in HepG2 cells to mediate BDE-100-induced toxicity

Abstract: To reduce flammability and meet regulatory requirements, Brominated Flame Retardants (BFRs) are added to a wide variety of consumer products including furniture, textiles, electronics, and construction materials. Exposure to polybrominated phenyl ethers (PBDEs) adversely affects the human health. Bearing in mind that (i) PBDEs are potentially toxic, (ii) the mechanism of PBDE toxicity is unclear, and (iii) the importance of the autophagy to the field of toxicology is overlooked, this study investigates whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…However, the studies on the roles of autophagy in PBDEs toxicity are still lacking. Limited studies reported that both PBDE-100 and PBDE-153 treatment resulted in accumulation of autophagosomes involved in HepG2 cells injury 35, 36. In the present study, PBDE-47 triggered autophagosomes accumulation identified by the increased double-membrane autophagosome vesicles, LC3-positive puncta and levels of LC3-II both in vivo and in vitro .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, the studies on the roles of autophagy in PBDEs toxicity are still lacking. Limited studies reported that both PBDE-100 and PBDE-153 treatment resulted in accumulation of autophagosomes involved in HepG2 cells injury 35, 36. In the present study, PBDE-47 triggered autophagosomes accumulation identified by the increased double-membrane autophagosome vesicles, LC3-positive puncta and levels of LC3-II both in vivo and in vitro .…”
Section: Discussionsupporting
confidence: 55%
“…More importantly, inhibition of autophagy by 3-MA also diminished PBDE-209-induced apoptosis in primary hippocampal neurons 40, supporting our findings and suggesting that targeting inhibition of autophagy may be a promising therapeutic target for the prevention and treatment of PBDEs neurotoxicity. Interestingly, some other studies also showed that apoptosis was enhanced upon inhibition of autophagy with WM in HepG2 cells following PBDE-100 or PBDE-153 treatment 35, 36, perhaps due to differences in the cell-type specificity and congener structure.…”
Section: Discussionmentioning
confidence: 97%
“…Following BDE-100 exposure, HepG2 cells had increased staining with lysosomal dye. The study also noted that the mitochondrial DNA copy number decreased in these cells, signifying an attempt from the cell to manage mitochondrial damage by selective mitophagy [83].…”
Section: Discussionmentioning
confidence: 84%
“…This is consistent with a recent study using a BDE‐100, another brominated flame retardant, which also caused autophagy in HepG2 cells. [ 24 ] It is also known that rises in intracellular Ca 2+ levels, as demonstrated for HBCD in our previous studies, [ 6,14,19 ] can activate Calmodulin‐dependent protein kinase kinase‐β (CamKKβ) which is an upstream kinase for AMP‐activated protein kinase, a key activator of autophagy. [ 25 ] This Ca 2+ ‐dependent process could therefore be the mechanism by which autophagy is activated by HBCD.…”
Section: Discussionmentioning
confidence: 99%